Revealing the gas recycling in the Circumgalactic Medium (CGM) utilizing a luminous lya nebula around a type II quasar at z = 2.6 with the Keck Cosmic Web Imager (KCWI) - Zhang, Shiwu; Cai, Zheng; Xu, Dandan; Afruni, Andrea; Wu, Yunjing; Wang, Wuji; Battaia, Fabrizio Arrigoni; Li, Mingyu; Wang, Sen; Bi, Xianzhi (The astrophysical journal, 2023)
How galaxies acquire material from the circumgalactic medium is a key question in galaxy evolution. Recent observations and simulations show that gas recycling could be an important avenue for star formation. This paper presents Keck Cosmic Web Imager integral field unit spectroscopic observations on a type II quasar, Q1517 + 0055 at z = 2.65, a pilot study of our Lyα nebulae sample at z ≈ 2. We revealed diffuse emission of the Lyα 1216, He ii 1640, and C iv 1549 on the projected physical scale of 122, 45, and 79 kpc, respectively. The total Lyα luminosity is L Lyα = 3.04 ± 0.02 × 1044 erg s−1. The line ratio diagnostics shows that He II/Lyα ≈ 0.08, and C IV/Lyα ≈ 0.28, consistent with the photoionization including recombination and photon pumping. We also identify the associated H i and C iv absorption from the spectra. By fitting the spectra, we derive both the column density and the velocity. We find that the velocity profile from both the absorption and the He ii emission exhibit increasing trends. Moreover, both the line ratio diagnostic from the emission and the column density ratio from the absorption confirm that the cool gas metallicity is ≥Z ⊙. From detailed modeling and estimation, gas recycling might be a more plausible interpretation compared with the scenario of a powerful outflow.
Veröffentlicht: 21. Juli 2023
Gesehen am 22.08.2023